Pemikiran Muhammad Nasir Dalam Sejarah Politik Indonesia 1930-1950 - Fadillah Fajri, Nur; Yosephine Sinurat, Junita; Istiana, Khoirul (Krinok: Jurnal Pendidikan Sejarah dan Sejarah, 2024)
This research was conducted to find out understand Muhammad Natsir's thoughts on political developments in Indonesia, the implementation or role of Muhammad Natsir's thoughts in the development of political history in Indonesia and the impact of Muhammad Natsir's political thoughts on the development of Indonesian political history. This condition made Natsir try to fight for the ideals of the Indonesian state, namely breaking free from the shackles of colonialism through his thoughts and struggle. Muhammad Natsir, who is familiarly called Pak Natsir, is a politician, cleric and intellectual who has simplicity in all his leadership. He first entered politics in 1930. The research method used in the research is the historical research method which consists of heuristics, source criticism, interpretation and historiography. The data used is through library research obtained from library and internet sources. The results of this research are Natsir's activities and thoughts which encourage Indonesian political activities to come back to life, such as the concepts of democracy, secularism and his struggle in the parliamentary assembly of the Republic of the United States of Indonesia (RIS). Thus, the impact of the thinking carried out is that the notion of secularism in Indonesian politics is eroded and replaced with the democratic values of Pancasila, the existence of political party activities, and the return of the Unitary State of the Republic of Indonesia (NKRI) from the United Republic of Indonesia (RIS).